Efeito antitumoral do extrato de carotenoides e biomassa de microalgas Scenedesmus obliquus em células de melanoma: envolvimento da sinalização purinérgica - Jesus, Loren Stephanie Borba de (2023)
Cutaneous Melanoma (CM) is an aggressive and metastatic tumor, resulting in low survival and high mortality rates. Despite significant advances in therapeutics, the disponible drugs are often undefective and related to resistance in the long term. Purinergic signaling has emerged as a potential pathway to cancer therapy due to its involvement in cell communication, proliferation, differentiation, and apoptosis. Actually, carotenoids from microalgae have been investigated in anti-melanoma therapy, due to safety and acceptable clinical tolerability. Thus, the objective of this work is to investigate the anti-melanogenic effect of carotenoids (CA) and total biomass (BM) from microalgae Scenedesmus obliquus on two cell lines (A375 and B16- F10) of cutaneous melanoma. Cells were cultivated under ideal conditions and treated with 10, 25, 50, and 100 μM of CA and BM separately for 24 hours. The effects of the compounds on viability, colony formation capacity, oxidant status, and purinergic signaling were verified. Our results showed that CA and BM decreased cell viability at IC50% 24,29 μM and 74,85 μM in B16-F10 and 73,93 μM and 127,80 μM in A375 lineages respectively. Also, both CA and BM isolated and associated with chemotherapy cisplatin (CIS), positively modulate ATP levels in levels in B16-F10 and A375 lineages through P2X7 manner and leading to cell apoptosis and immunoregulation through activation of A2A receptors and CD73 blockage. Together, the results reveal that the CA and BM from S. obliquus display an anti-melanogenic effect, inhibiting melanoma cells and providing the basis for therapeutic strategies for melanoma.